The Problem of Modern Man in Indonesia and Its Solution According to Seyyed Hossein Nasr - Dedy Irawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2022)
Abstract The problem of modern man and Western civilization, have caused man in general to forget the nature of his life, particularly in Indonesia. Various kinds of damage, starting from theology, environment, sciences, and other aspects do not escape the consequences of modern man actions. Metaphysics and the real reality of God along with the development of technology, disappeared and replaced with false reality that will destroy the existence of human being itself. Many western scientists agree that human nature is increasingly shortened as modern science and technology evolve, which is empty of metaphysics recognition. Furthermore, modern man today only lives on the edge of his existence and the reality of nature. If they don’t immediately aware of this situation, they have pushed themselves to the brink of physical and spiritual extinction. This research tries to uncover some of Seyyed Hossein Nasr's criticisms and solutions to modern man problems in several aspects such as scientific errors, environmental crises, telology, and cosmology by using literature studies with descriptive analytical methods for general, and for Indonesian in particular. This research draws the following conclusions; First, to deal with the theological problems that deny God's reality, Nasr offered solutions to perennial philosophy and sufism. Second, in facing the mis-concept of the cosmos, Nasr made Islamic Cosmological doctrine as the key. Third, to deal with the worsening environmental crisis, Nasr invites people to make Nature as Sacred creation of God. And finally, the fourth, Nasr offers the concept of Sacred Science, as a solution to the degradation of metaphysical and spiritual values in modern science. Regarding that Indonesia is a big nation, Indonesia needs to apply the Nasr concept as a solution to the destruction of modern man.